Mereposisi Fungsi Menhir dalam Tradisi Megalitik Batak Toba - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2017)
AbstractThe functions of menhirs are often being connected to medium of worship, burial markers, and guardian of an area/village, or stakes to tether sacrificial animals. Such functions are known to be related to visual aspect or practical functions. Menhirs in Batak Toba culture on Samosir Island, which are called tunggalpanaluan and borotan also have the above functions. Moreover, the cultural items have other functions in relation to the aspect of cosmogony. Hence the aim of this article is to understand the function of tunggalpanaluan and borotan in relation to cosmogony, which were carried out using descriptive-interpretative method, supported by ethnographical data of Batak Toba culture that was compared to similar cultures and functions in other places. The implementation of the method to fulfill the research aim reveals that tunggalpanaluan and borotan also function as a bridge to connect the three levels of environment. AbstrakKerap fungsi menhir itu dikaitkan dengan medium pemujaan, tanda kubur, penjaga area/perkampungan atau tambatan hewan kurban. Fungsi dimaksud diketahui terkait dengan aspek visual atau fungsi yang bersifat praktis. Menhir dalam budaya masyarakat Batak Toba di Pulau Samosir yang disebut dengan tunggal panaluan dan borotan juga memiliki fungsi dimaksud. Kedua benda budaya itu juga memiliki fungsi lainnya yang terkait dengan aspek kosmogoni. Berkenaan dengan itu maka tujuan uraian ini adalah mengtahui fungsi tunggal panaluan dan borotan dalam kaitannya dengan kosmogoni. Hal tersebut dilakukan melalui metode deskriptif-interpretatif yang disertai data etnografi budaya Batak Toba untuk kemudian dibandingkan dengan budaya dan fungsi sejenis di tempat lainnya. Pemanfaatan metode tersebut dalam pencapaian tujuan penelitian menghasilkan fungsi tunggal panaluan dan borotan sebagai jembatan bagi roh untuk menyatukan ketiga tingkatan alam.